Preliminary data on centipedes (Chilopoda: Scolopendromorpha and Scutigeromorpha) in Ta Xua natural reserve, Son La Province, Vietnam - Thanh Binh, Tran Thi; Hung, Nguyen Duc; Loan, Ha Kieu; Ha, Vu Thi (Academia Journal of Biology, 2018)
Study on centipedes was conducted in Muong Thai commune, Ta Xua Natural Reserve, Son La in May and November 2017. Samples were collected in four typical habitats: natural forests, bamboo mixed forests, bamboo forests and agro-residental areas. As a result, a total of 17 species and subspecies in two orders (Scolopendromorpha and Scutigeromorpha) was recorded in that region. Of which, the order Scolopendromorpha has 15 recorded species and subspecies belonging to 7 genera, 3 families (Cryptopidae, Scolopendridae, Scolopocryptopidae). The other order, Scutigeromorpha, has only one species in one family (Scutigeridae). The study results also contributed new records of 13 species in 7 genera to the centipede fauna of the northwestern part of Vietnam, and 1 genus, Thereuonema, to the Vietnamese fauna. Among four habitats, natural and bamboo forests have highest similarity on species composition, but agro-residental area and bamboo forest have lowest value on species composition. The diversity index (H’) is highest in bamboo forests (2,98), decreases in mixed forest (2,31), natural forest (1,67) and agro-residental area (0,74). In contrast, centipede density is highest in natural forest (0,60 ind./m2), reduces in bamboo forest (0,47 ind./m2) and mixed forest (0,20 ind./m2).